(untitled) (Blockchain Technology and Distributed Systems, 2021)
Over the past ten years it has been demonstrated that the market for digital assets is growing significantly. It is no longer considered a kind of a niche concept, but rather has turned into a multi-trillion-dollar industry. Now, that the crypto-assets are gaining popularity with institutional investors, asset managers, as well as ordinary everyday investors, it has become important to have one clear and coherent framework within which such assets can be placed. In Europe, the remarkable implementation of the Markets in Crypto-Assets Regulation (MiCA) represents a paradigm shift on the continent’s philosophy towards cryptocurrency regulation, providing sorely needed clarification and safeguards and enhancing processes that seek to promote competition and creativity in the financial services business[i]. The legal structure overview of Cryptocurrency related assets in the European union had been historically complex and yet incomplete, wherein each member worked out its own system of treatment of the digital assets and the blockchain technology. This has posed huge obstacles to cross-border companies as the compliance level varied considerably between jurisdictions. For instance, on the other side, France occupied a robust position through the development of bespoke tools to develop a framework for the ICO in 2019, but other countries like Germany were kinder where they used existing other forms of selling and marketing tools of financial deployment. The absence of a regulatory harmonization caused the European economic area (EEA) to miss the European opportunities for the crypto evolution, and risks emerged for institutional clients that wanted to do business with that market. [i] European Securities and Markets Authority (ESMA), "Crypto-assets and ICOs: ESMA’s Response to the European Commission’s Call for Evidence," February 2019.